Laparoscopic sigmoid colectomy for diverticulitis – stricture: A case report with review of literature (Indian Journal of Case Reports, 2024)
Diverticulosis is a common condition in the western world. It is often asymptomatic. However, its inflammation and the occurrence of its complications precipitate symptoms. Uncomplicated diverticulitis can be managed conservatively, most of the times. Complicated diverticulitis may need an endoscopic, interventional radiological, or surgical intervention. Herein, we report the case of a 53-year-old patient with complicated sigmoid diverticulitis, i.e., stricture caused by repetitive attacks of acute diverticulitis, who underwent a laparoscopic sigmoid colectomy followed by primary anastomosis.